Leiomyoma in Retzius’ space: An unusual location - Niwa, Naoya; Yanaihara, Hitoshi; Horinaga, Minoru; Asakura, Hirotaka (Canadian Urological Association Journal, 2013)
We report the case of a 54-year-old woman who presented to our hospital with microscopic hematuria. An imaging study revealed a tumour in the Retzius’ space. The tumour was surgically removed by an abdominal approach. Pathological examination revealed aleiomyoma. This case demonstrates a leiomyoma in an unusual location.